2021
DOI: 10.1155/2021/5291858
|View full text |Cite
|
Sign up to set email alerts
|

Management of a Hypomineralisation of the Enamel by Applying a Remineraliser Based on Zinc Hydroxyapatite (microRepair)

Abstract: According to our experience, the treatment with remineralising mousse based on biomimetic nanohydroxyapatite has the advantage of being easily implemented by all patients as it is economical and absolutely noninvasive. The following case report reports the results obtained from the use of a mousse based on biomimetic nanohydroxyapatite for the treatment of incisor and molar hypomineralisation. This case report illustrates the case of a 4-year-old patient who was diagnosed with MIH and was subjected to reminera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 18 publications
0
9
0
2
Order By: Relevance
“…(Bakkal et al, 2017;Biondi et al, 2017;Restrepo et al, 2016). This approach is based on the concept that increasing the mineral component in teeth affected by MIH can lead to an improvement of the physical structure of the enamel together with its aesthetic appearance, and to the decrease of dental sensitivity (Solinas et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(Bakkal et al, 2017;Biondi et al, 2017;Restrepo et al, 2016). This approach is based on the concept that increasing the mineral component in teeth affected by MIH can lead to an improvement of the physical structure of the enamel together with its aesthetic appearance, and to the decrease of dental sensitivity (Solinas et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Molar–incisor hypomineralization (MIH) is a delimited qualitative developmental defect leading to several dental complications, like hypersensitive teeth, increased susceptibility to caries, impaired chewing due to rapid tooth loss, and aesthetic defects; this condition may significantly affect patients' quality of life, so a correct diagnosis and treatment plan are strictly required (Solinas et al, 2021). To date, different clinical trials have been conducted to evaluate the efficacy of remineralizing agents like fluoride in different formulations, casein‐based mousses and amorphous calcium phosphate (CPP‐ACP), and hydroxyapatite (Bakkal et al, 2017; Biondi et al, 2017; Restrepo et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by Solinas et al [17] reported that the application of biomimetic nanohydroxyapatite for the treatment of incisor and molar hypomineralization for six months in a 4-year-old patient resulted in a significant decrease in the hypersensitivity and improved the enamel appearance for the maxillary incisors. Further studies to evaluate the effect of biomimetic nanohydroxyapatite are recommended in hope that more invasive treatment options can be avoided.…”
Section: Discussionmentioning
confidence: 99%
“…Conservative methods for remineralization usually include proper oral hygiene measures, which requires patient's compliance and involves multiple applications of fluorides, and/or casein phosphopeptide-amorphous calcium phosphate containing products [14,15]. Recently, a few studies reported that the use of biomimetic hydroxyapatite containing toothpaste forms a coating on the enamel surface, promotes superficial enamel repair, and aids in preventing secondary caries around restorations [16,17,18].…”
Section: Introductionmentioning
confidence: 99%